Divergência funcional em espécies congêneres sintópicas: estudo de caso com Mimosa spp - Ponte, Fabiann Lucena da (2013)
Explain the coexistence of plant species is still very controversial, since they require the same set of environmental resources. In severe abiotic conditions, although theoretically environmental filter select phylogenetically closely related species sharing the limiting resource is likely due to functional divergence in strategies to reduce the effect of competitive interactions and enable coexistence. The water resource is considered the main limitation in tropical climates in arid and semiarid. Study the hydraulic architecture of congeneric species and codominant co occurring these environments can help you understand which strategies differential use of water and allow the establishment coexist. We studied Mimosa tenuiflora (Willd) Poir., And Mimosa caesalpiniifolia Benth., Both abundant and co occurring in caatinga, semi-arid area of Northeast Brazil. We analyzed the specific leaf area, leaf mass per area, density of the wood, the anatomy of the stem xylem and branch hydraulic conductivity potential, leaf water potential and gas exchange, and the resistance of the xylem Cavitation and embolism. Species showed similar wood density, but the anatomy of the stem xylem showed that M. tenuiflora has higher vessel density and higher weighted average diameters. The two species differ in architecture and operating hydraulic and stomatal sensitivity to water stress. M. tenuiflora is always green, exhibits behavior indicative anisohídrico and hydraulic architecture hydraulic transport safer, and greater resistance to drought. Consequently, this species can keep the leaves in the period of greatest water stress. Mimosa caesalpiniifolia is deciduous, exhibits behavior indicative isohydric and hydraulic architecture hydraulic transport more efficient and more vulnerable to drought. Thus, we demonstrate that phylogenetically closely related species, which coocorrem in environments with strong environmental filter for coexist must differ functionally and therefore there is no phylogenetic niche conservation.